(untitled) (Res Gesta, 2021)
In the article we enquire about the profile and trajectory of Enrique Romero Brest, a key reference in the conformation of the disciplinary field of school physical education. In this way, we question about his formation, the links he established, his entrance in the rows of the Estate and the work developed, which turn him into a professional and intellectual to the service of the Estate. The production of knowledge that he developed in the Instituto Superior de Educación Física and the diffusion in various publications, they turn him into a specialist and therefore into a legitimate authority of this disciplinary field. At the same time he generated knowledge of Estate which had as a purpose the contribution to the physical perfectionism and body health of the individuals who formed the future of the country.